Understanding differentiated instruction - Tomlinson, Carol A. ([Alexandria, Va.] : ASCD, 2017)
Provides a guide for teachers that looks at differentiated instruction that focus on key terms, getting started, critical pointers, and other topics.
Professional.
Professional
Keywords: Cognitive styles in children; Individualized instruction; Mixed ability grouping in education; Ability grouping in education; Cognitive styles in children; Individualized instruction; Instructional and educational works